Development of a method for energy efficiency optimization of an autonomous, electric vehicle on the test track for automated and connected driving in Hamburg - Benedikt Buhk (Hochschule für Angewandte Wissenschaften Hamburg, 2023)
This study introduces a simulation model that couples a forward facing energy model with a microscopic traffic simulator for the analysis of the energy performance of connected and autonomous vehicles (CAVs). The developed model is validated against measurement data from driving cycles of an Electric Vehicle (EV). The applicapability of the model is demonstrated by optimizing a driving algorithm on energy efficiency.
Keywords: energy efficiency; driving algorithms; electric vehicle; traffic simulation; forward-facing energy model; Energieeffizienz; Fahralgorithmen; Elektrofahrzeug; Vehrkehrssimulation; vorwärts-gerichtetes Energie Model